Visual preferences for the development of a Malaysian garden identity - Kaboudarahangi, Mina; Mohd Tahir, Osman; Mohd Shariff, Mustafa Kamal; Maulan, Suhardi (American-Eurasian Network for Scientific Information, 2011)
Malaysia is a developing country that has been experiencing rapid development since its independence in 1957. The country-with its unique natural and cultural heritage-is in need of projecting its own landscape identity through the development of a distinct national garden identity. This paper discusses a study that used Content Identifying Methodology to determine Malaysian public preferences among the iconographies of four selected well-established gardens, with the purpose of determining visual preferences of Malaysians for their own developing gardens. The results of the study found that plants, water, and traditional architectural features imbued with meaning were the preferred elements for a Malaysian garden. Respondents also indicated preferences for garden layouts that possessed legibility and mysterious qualities. These findings are useful for policy makers and landscape professionals with an interest in developing gardens with a Malaysian identity. These findings could also throw some light on other developing gardens, especially those in newly developed countries.